The role of assurance within project management standards - Koch, Ondřej; Oškrdal, Václav; Bílík, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2016)
The thesis is focused on the role of assurance within project management standards. Firstly, the theoretical role of assurance was established based on the performed research. Three main areas of interest have been identified: Assurance over business, the project itself and the product. The role established in the theoretical part of the work was subsequently compared to information systems development methodologies and project management standards. From the comparison with AUP, Scrum and FDD methodologies, it seems that the better assurance is defined, the longer the feedback cycle is. During the comparison with the three most widespread project management standards - IPMA, PRINCE2 and PMBOK - various areas have been identified where these are not fully compliant with the theoretical role of assurance. Additions to IPMA and PMBOK have been created to support the compliance with the theoretically established role of assurance, fulfilling the objective set for the practical part of the work and providing benefits to IT project management professionals that struggle to deliver quality products while following one of the aforementioned standards.
Vedoucí práce: Václav Oškrdal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses